2022
DOI: 10.1093/g3journal/jkac146
|View full text |Cite
|
Sign up to set email alerts
|

QTLViewer: an interactive webtool for genetic analysis in the Collaborative Cross and Diversity Outbred mouse populations

Abstract: The Collaborative Cross (CC) and the Diversity Outbred (DO) mouse populations are related multiparental populations (MPPs), derived from the same eight isogenic founder strains. They carry >50M known genetic variants, which makes them ideal tools for mapping genetic loci that regulate phenotypes, including physiological and molecular traits. Mapping quantitative trait loci (QTLs) requires statistical and computational training, which can present a barrier to access for some researchers. The QTLViewer so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…iPSCs also enable differentiation into other cell types, 3-dimensional cell models, organoids, or scaffolded arrays which can be screened across a variety of environmental conditions including other toxicants, drugs, or other culture conditions. It is important to note that while other studies mapping cmQTL were limited by lack of genetic diversity, poor adaptation of some cell types to culture, and the genetic architecture of the population being studied 2,97 , we also found that beyond large effect QTL, our study was underpowered despite previous examples showing sample sizes in this range for molecular phenotypes can detect strong QTL 12,54,98 . This is the result of experimental and residual sources of variance as described above, as well as the limited extensibility of standard dose-response models to diverse populations.…”
Section: Discussionmentioning
confidence: 56%
“…iPSCs also enable differentiation into other cell types, 3-dimensional cell models, organoids, or scaffolded arrays which can be screened across a variety of environmental conditions including other toxicants, drugs, or other culture conditions. It is important to note that while other studies mapping cmQTL were limited by lack of genetic diversity, poor adaptation of some cell types to culture, and the genetic architecture of the population being studied 2,97 , we also found that beyond large effect QTL, our study was underpowered despite previous examples showing sample sizes in this range for molecular phenotypes can detect strong QTL 12,54,98 . This is the result of experimental and residual sources of variance as described above, as well as the limited extensibility of standard dose-response models to diverse populations.…”
Section: Discussionmentioning
confidence: 56%
“…We used a modified version of RQTL2 and qtl2qpi to identify chromosomal regions associated with survival after MRSA infection [53, 54]. We used the number of mice within a strain that survived at the end of each day as the phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…We used RQTL2 software with CC genotypes imputed from qtl2qpi to identify genomic regions associated with survival after MRSA infection [59, 60]. Within the CC strains we infected, survival was a highly heritable trait with a broad sense heritability score of 0.38 (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…All analyses were performed using the R package qtl2 101 . Processed data and results are uploaded to the QTLViewer webtool (https://churchilllab.jax.org/qtlviewer/Zimring/RBC; 103 ) for interactive analyses and download. All data and code for the analysis pipeline are available at figshare (https://doi.org/10.6084/m9.figshare.24456619).…”
Section: Star Methodsmentioning
confidence: 99%